The Fight for Nocera. Conspiracy and Vendetta Against the Trinci Brothers in Croniche di Lucca - Szolnoki, Zoltán (City and War, 2022)
Giovanni Sercambi (1348–1424) wrote on several acts of violence in his main work, entitled Croniche di Lucca. On the pages of his chronicle we can often read about vendettas, factional fights and the guilty of traitors. As regards to the latter category, the most important ones were probably the killing of Lazzaro Guinigi, Lord of Lucca in 1400, and the conspiracy against the Trinci brothers. Nicolaò and Bartolomeo Trinci were killed in 1421 by Pedro de Argillaia castellano, in the fortress of Nocera, which was the property of them. The third brother Corrado Trinci and his allied troops immediately moved to Nocera. Braccio da Montone, signore of Perugia (and famous condottiero) participated in the campaign. The army recaptured Nocera and the conspirators died. Giovanni Sercambi wrote one of the longest chapters of his historical work about the death of Niccolò and Bartolomeo Trinci. The interest of the Luchese writer is unquestionable. In contrast to the other Tuscan writers, none of whom mentions the bloody events of 1421. In my present paper, I examine the motives behind Sercambi’s account. Jean-Baptist Delzant wrote about it recently, but I approach the context differently. With the comparing analysis and the research of the contemporary political circumstances and family relations I conclude that Sercambi’s personal interest in violent events and his teaching will was only one reason. On the other hand the writer was sensible to the Guinigi’s external politics. He knew the difficult situation in external politics: the Guinigi had marriage relations with the Varani of Camerino and the Trinci of Foligno. Giovanni Sercambi could get information from the Trinci wife of Paolo Guinigi. In the light of this, I examine the special elements of the Sercambi-kind storytelling.